(Novels) Idiom , evolution and properties in the light of critic Shugaa Muslim Al-Aani (Journal of the College of Education for Women, 2019)
A critics ,Shugaa Muslim Al-Aany, has specific critical principles in his branchclassifications for the type of the novel that is linked with its sources and what is adoptedof critical approaches and curriculums. The novel by its type as a literary one hasoccupied Al-Any's critical importance very much ,he has divided it historically accordingto its historical development ,the impact of dr.Abd Al-Muhassen Tha Badr's divisions onAl-Any cannot hidden.In his speech about the origin of novel and story art generally , Al-Any becomesbetween the acknowledgement of the affect of Al-Mgma in rising of this art and denied itsaffect at last. He has classified the novel also as a stylistic classification:(an impressionistnovel);(A novel of current of consciousness);( a novel of time density),(a scene novel);(Al-Musrwah);(a monologue novel) or(a novel of the one sound);(polyphone)or (polyphonies) ;(a novel of Narcissistic structure) .Besides ,he depends on the social and philosophicalprinciples when he has classified the novel into (the old social novel)and (the newdramatic novel).The one can see confusion in his classifications of the novel (JalelKhaled),he has classified it as the first artistic analytical novel ,a romantic one once , aneducational in another time, But the critics realize that this confusion that fall within it ,sohe restudies it for decades to prove that it is a intellectual acculturation and rearingalthough it violates in its art other novels of the same generation.